INNOVATION AND PERFORMANCE: AN ANALYSIS OF SUSTAINABLE FIRMS IN BRAZIL AND EUROPE - Santos, José Glauber Cavalcante dos; Vasconcelos, Alessandra Carvalho de; De Luca, Márcia Martins Mendes; Cunha, Jacqueline Veneroso Alves da (Revista Universo Contábil, 2019)
In this study we analyze whether the innovation profile of sustainable Brazilian and European firms produces a difference in economic performance. Resource-Based View (RBV) posits that innovation, due to uniqueness and heterogeneity, leads to competitive advantage and improved performance. Data was collected from 78 sustainable firms covering the period 2010-2013 and analyzed with the Mann-Whitney test and the Kruskal-Wallis test. Four perspectives on innovation were considered: R&D, intangible innovation assets, patents, and disclosure. Economic performance was expressed as return on assets and return on equity. Innovation contributed to superior performance (though not significantly), but the claim that innovation generates competitive advantage could not be validated. Our results suggest the existence of a hypothetical curve of efficiency determined by diversification of innovation since higher levels of innovation were not necessarily related with greater performance. This may be explained by the assumption of heterogeneity, according to RBV. The study provides subsidies for managers looking to optimize investments in innovation, increasing the efficiency of resources and boosting differentiation in different economic scenarios.